LINGUODIDACTIC FEATURES MASTERING GRAMMAR TERMS STUDENTS 8―9 GRADES - Dyka, Natalia M. (Educological discourse, 2015)
The article discusses the features of the assimilation of grammatical concepts students 8-9 classes of secondary schools. Topical is the creation of new approaches to the study of grammatical concepts at students of secondary schools in the study of grammar. Effective organization of education in the school due to the syntax into account the peculiarities of typology, structure, planning, preparation, construction and organization of the modern Ukrainian language classes, as well as development trends. Isolated and grounded stages of the process of assimilation of grammatical concepts in modern linguistics. Presented system of exercises aimed at the assimilation of grammatical concepts primary school students in the study of syntax.